Expelled hypopharynx myxoid liposarcoma: a rare entity to consider - Gómez-Rázuri, Katherine (2024)
Introduction: The diagnosis of sarcoma in the head and neck is unusual, so the case of a 53-year-old female patient with myxoid liposarcoma in the hypopharynx is reported due to its rarity in this location. Case of report: Clinically, tumor growth is associated with dysphagia, dysphonia, and obstruction. Imaging characteristics may contribute in a magnetic resonance study; however, the definitive diagnosis is histological and genetic. This diagnosis is often difficult and generally only recognized with recurrences. The treatment of choice is surgical with or without chemotherapy/radiotherapy, with myxoid liposarcoma being particularly radiosensitive. Conclusion: Local recurrence is common, but metastasis seldom occurs. This case contributes to Latin American literature and emphasizes the importance of early recognition of the disease, considering the required histological characteristics.